4(2x+3)=3x-(2x-2)

Simple and best practice solution for 4(2x+3)=3x-(2x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+3)=3x-(2x-2) equation:


Simplifying
4(2x + 3) = 3x + -1(2x + -2)

Reorder the terms:
4(3 + 2x) = 3x + -1(2x + -2)
(3 * 4 + 2x * 4) = 3x + -1(2x + -2)
(12 + 8x) = 3x + -1(2x + -2)

Reorder the terms:
12 + 8x = 3x + -1(-2 + 2x)
12 + 8x = 3x + (-2 * -1 + 2x * -1)
12 + 8x = 3x + (2 + -2x)

Reorder the terms:
12 + 8x = 2 + 3x + -2x

Combine like terms: 3x + -2x = 1x
12 + 8x = 2 + 1x

Solving
12 + 8x = 2 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
12 + 8x + -1x = 2 + 1x + -1x

Combine like terms: 8x + -1x = 7x
12 + 7x = 2 + 1x + -1x

Combine like terms: 1x + -1x = 0
12 + 7x = 2 + 0
12 + 7x = 2

Add '-12' to each side of the equation.
12 + -12 + 7x = 2 + -12

Combine like terms: 12 + -12 = 0
0 + 7x = 2 + -12
7x = 2 + -12

Combine like terms: 2 + -12 = -10
7x = -10

Divide each side by '7'.
x = -1.428571429

Simplifying
x = -1.428571429

See similar equations:

| 10(3-x)=-4x-6 | | 2a+8=54 | | -12=-5-6x+11 | | D+-8d+7=0 | | 2x+12+6x-10=180 | | -0.06y+0.08(1100-y)=0.36y | | 8x+12=9x+5 | | -5a-5(1-4a)=-5+4a | | 2(4+x)=4x+3 | | 5x-16=4x+7 | | 4x+3x=6x-6 | | 57=3y | | 3y+1=28 | | 5x-20=2x+4 | | 5d-2=63 | | -0.06y+0.08(1100-y)=0.36 | | 4x+3x=6x | | -3x+9=2x-6 | | 9n-12=69 | | 3y+14=5 | | -6x-17=-4x+7 | | 8(x+2)=3x+5 | | -11*3=15+-6*3 | | 7.8p-18=2.6p-5 | | 3x+8x-40=48 | | 9(x-5)=8(x-1) | | -96+5x=-8x+86 | | 2x+2=x+56 | | -3n-4=-2-3n | | 12x+14y=112 | | D-8d+7= | | 5x+2-x=2(x+3) |

Equations solver categories